Evaluation of Labour Care Guide: Labor progression in obese women from Basra, Iraq - Sabreen MM Alkhulaifi; Sajidah Al-Rubaai; Marwah Sadeq Mustafa Almansor (Romanian Medical Journal)
The prevalence of maternal obesity has emerged as a significant global public health issue. The World Health Organization (WHO) has just introduced a revolutionary tool known as the WHO Labour Care Guide for the purpose of monitoring the well-being of mothers and infants throughout the process of labor. The study aims to evaluate the impact of obesity on the progression of labor, mode of delivery, and subsequent neonatal complications. Our research was conducted on 176 women who fulfilled the inclusion criteria at Basra Maternity and Child Hospital, the number of women with normal BMI was 100, while the class 1 obese was 76 cases. The results show the risk of emergency caesarean section is significantly increased among the class 1 obese woman, the percentages were 40.7%, and 14% respectively (p-value <0.001), regarding the neonatal outcome assessed by the APGAR scoring system, there was a relatively low APGAR score among the total deliveries of class 1 obese women regardless of the mode of delivery, (p-value was significant <0.001) compared with the average Body Mass Index women, the neonatal birth weight was significantly different between the two Body Mass Index groups, there is an increase in the birth weight among class 1 obese women (p-value <0.001). The study concludes obesity has a substantial influence on the increased incidence of caesarean section deliveries among women classified as having obesity class I, and there is a positive correlation between body mass index and the desire for oxytocin administration among obese women.